Melanocyte-keratinocyte cross-talk in vitiligo - Touni, Ahmed Ahmed; Shivde, Rohan S.; Echuri, Harika; Abdel-Aziz, Rasha T. A.; Abdel-Wahab, Hossam; Kundu, Roopal V.; Le Poole, I. Caroline (Frontiers in Medicine, 2023)
Vitiligo is a common acquired pigmentary disorder that presents as progressive loss of melanocytes from the skin. Epidermal melanocytes and keratinocytes are in close proximity to each other, forming a functional and structural unit where keratinocytes play a pivotal role in supporting melanocyte homeostasis and melanogenesis. This intimate relationship suggests that keratinocytes might contribute to ongoing melanocyte loss and subsequent depigmentation. In fact, keratinocyte dysfunction is a documented phenomenon in vitiligo. Keratinocyte apoptosis can deprive melanocytes from growth factors including stem cell factor (SCF) and other melanogenic stimulating factors which are essential for melanocyte function. Additionally, keratinocytes control the mobility/stability phases of melanocytes via matrix metalloproteinases and basement membrane remodeling. Hence keratinocyte dysfunction may be implicated in detachment of melanocytes from the basement membrane and subsequent loss from the epidermis, also potentially interfering with repigmentation in patients with stable disease. Furthermore, keratinocytes contribute to the autoimmune insult in vitiligo. Keratinocytes express MHC II in perilesional skin and may present melanosomal antigens in the context of MHC class II after the pigmented organelles have been transferred from melanocytes. Moreover, keratinocytes secrete cytokines and chemokines including CXCL-9, CXCL-10, and IL-15 that amplify the inflammatory circuit within vitiligo skin and recruit melanocyte-specific, skin-resident memory T cells. In summary, keratinocytes can influence vitiligo development by a combination of failing to produce survival factors, limiting melanocyte adhesion in lesional skin, presenting melanocyte antigens and enhancing the recruitment of pathogenic T cells.